2006
DOI: 10.1104/pp.106.080093
|View full text |Cite
|
Sign up to set email alerts
|

The Ethylene-InsensitivesickleMutant ofMedicago truncatulaShows Altered Auxin Transport Regulation during Nodulation

Abstract: We studied the ethylene-insensitive, hypernodulating mutant, sickle (skl), to investigate the interaction of ethylene with auxin transport during root nodulation in Medicago truncatula. Grafting experiments demonstrated that hypernodulation in skl is root controlled. Long distance transport of auxin from shoot to root was reduced by rhizobia after 24 h in wild type but not in skl. Similarly, the ethylene precursor 1-amino cyclopropane-1-carboxylic acid inhibited auxin transport in wild type but not in skl. Aux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 69 publications
8
95
0
6
Order By: Relevance
“…Four auxin-responsive genes, GH3.1, SAUR1, ARF16a, and IAA9, were more strongly induced by S. meliloti in skl relative to the wild type ( Figure 5), consistent with enhanced auxin transport in skl (Prayitno et al, 2006), and reveals an unexpected role for auxin in root-hair infection. Although S. meliloti induced DR5-GUS in all root hairs in the infection zone, expression of GH3.1, ARF16a, and SAUR1 was restricted to infected cells, indicating that auxin signaling in infected and noninfected root hairs is distinct.…”
Section: Discussionsupporting
confidence: 50%
“…Four auxin-responsive genes, GH3.1, SAUR1, ARF16a, and IAA9, were more strongly induced by S. meliloti in skl relative to the wild type ( Figure 5), consistent with enhanced auxin transport in skl (Prayitno et al, 2006), and reveals an unexpected role for auxin in root-hair infection. Although S. meliloti induced DR5-GUS in all root hairs in the infection zone, expression of GH3.1, ARF16a, and SAUR1 was restricted to infected cells, indicating that auxin signaling in infected and noninfected root hairs is distinct.…”
Section: Discussionsupporting
confidence: 50%
“…It has been shown that some genes transcriptionally controlled by both nodulation and auxin transport inhibitors might be important for nodule initiation (Rightmyer and Long 2011). In agreement, physiological experiments in vetch, white clover and M. truncatula have revealed that at the nodule initiation site, a local inhibition of polar auxin transport takes place that might allow auxin accumulation at the site of nodule primordia development (Mathesius et al 1998;Boot et al 1999;Prayitno et al 2006;van Noorden et al 2006). Besides a local influence on auxin transport, the development of the first nodules reduces the long-distance shoot-to-root transport of auxins (van Noorden et al 2006) that might be fundamental to control nodule numbers (van Noorden et al 2006).…”
Section: More Root Organs: Nodule Formation Is Enhanced By Exogenous mentioning
confidence: 69%
“…Nodulation mutants that show pleiotropic phenotypes, such as har1, astray, crinkle, and lot1 in L. japonicus, and sickle and latd in M. truncatula (Krusell et al, 2002;Nishimura et al, 2002;Tansengco et al, 2003;Oka-Kira et al, 2005;Ooki et al, 2005;Prayitno et al, 2006;Liang et al, 2007), provide evidence for this statement. Our analysis of brush reveals a coupled effect on primary root growth and successful rhizobial infection.…”
Section: The Brush Phenotype Differs From That Of Previously Describementioning
confidence: 72%